THE ROLE OF FISCAL DECENTRALIZATION IN THE FORMATION OF FINANCIAL RELATIONSHIPS LOCALLY - Voznyak, H. V. (The actual problems of regional economy development, 2016)
The purpose of the article was the coverage of the theoretical aspects of fiscal decentralization and clarification of the effects of Ukraine in the process of expanding the powers of local authorities regarding management decisions on the formation and use of budgetary resources. In the article the essence and role of fiscal decentralization, analyzes foreign experience. Systematized features of formation of financial relationships locally. It is shown that fiscal decentralization should not be limited to the redistribution of resources between levels of government, and should encourage local communities to build financial capacity and strengthen their self-sufficiency. Proved that fiscal decentralization in Ukraine not completed the following steps to start the process of strengthening the material and financial base of local communities must lie in the plane of the analysis results traversed phase of fiscal decentralization, identifying its strengths and contradictions, and the implementation of fiscal decentralization should be based on administrative territorial reform and a new philosophy of government JEL: H 20